Hormone-induced DNA damage response and repair mediated by cyclin D1 in breast and prostate cancer - Di Sante, Gabriele (2018)
Cell cycle control proteins govern events that leads to the production of two identical daughter cells. Distinct sequential temporal phases, Gap 1 (G1), Gap 0 (G0), Synthesis (S), Gap 2 (G2) and Mitosis (M) are negotiated through a series of check points during which the favorability of the local cellular environment is assessed, prior to replicating DNA [1]. Cyclin D1 has been characterized as a key regulatory subunit of the holoenzyme that promotes the G1/S-phase transition through phosphorylating the pRB protein. Cyclin D1 overexpression is considered a driving force in several types of cancers and cdk inhibitors are being used effectively in the clinic for treatment of ERα+ breast cancer [1, 2]. Genomic DNA is assaulted by damaging ionizing radiation, chemical carcinogens, and reactive oxygen species (ROS) which are generated by cellular metabolism. Furthermore, specific hormones including estrogens [3, 4] and androgens [5] govern pathways that damage DNA. Defects in the DNA Damage Response (DDR) pathway can lead to genomic instability and cancer. Evidence is emerging that cyclin D1 bind proteins involved in DNA repair including BRCA1 [6], RAD51 [7], BRCA2 [8] and is involved in the DNA damage and DNA repair processes [7, 8]. Because the repair of damaged DNA appears to be an important and unexpected role for cyclin D1, and inhibitors of cyclin D1-dependent kinase activity are being used in the clinic, the latest findings on the role of cyclin D1 in mediating the DDR including the DDR induced by the hormones estrogen [9] and androgen [10, 11] is reviewed.